An old-new measure of canal water inequity - Anwar, Arif A.; Ul Haq, Z. (Informa UK Limited, 2013)
The fixed-turn or warabandi system of irrigation management is aimed at providing equitable rationing of Pakistan's limited water resources. This paper assesses the equity in practice of the warabandi system using the Gini and Theil indices. Defining equity as the delivery of an equal depth of water over the irrigated area for a crop season, distribution is relatively equitable at the distributary level. There is a need for improved indices that represent inequity and the difference between canal capacity and operational flows. This is particularly important for canals in the low- and lowest-priority subsets of the warabandi schedule.